A Dual‐Stimuli‐Responsive Coordination Network Featuring Reversible Wide‐Range Luminescence‐Tuning Behavior. (21st March 2019) - Yao, Zhao‐Quan; Xu, Jian; Zou, Bo; Hu, Zhenpeng; Wang, Kai; Yuan, Yi‐Jia; Chen, Ya‐Ping; Feng, Rui; Xiong, Jian‐Bo; Hao, Jialei; Bu, Xian‐He
Abstract: We herein report a new coordination network that deforms in a smooth and reversible manner under either thermal or pressure stimulation. Concomitantly, the organic fluorophores coordinatively bound to the channel in a face‐to‐face arrangement respond to this structural deformation by finely adapting their conformation and arrangement. As a result, the material exhibits a remarkable dual‐stimuli‐responsive luminescence shift across almost the entire visible region: The emission color of the crystal gradually changes from cyan to green upon heating and then to red upon pressure compression. Furthermore, each stage exhibits a linear dependence of both the emission maximum and intensity on the stimulus and is fully reversible.